Exclusive breastfeeding and maternal employment among mothers of infants from three to five months old in the Fafan zone, Somali regional state of Ethiopia: a comparative cross-sectional study - Frew Tadesse; Yonas Alemayehu; Sisay Shine; Henok Asresahegn; Trhas Tadesse (BMC, 2019)
Abstract Background Lack of exclusive breastfeeding is the most important risk factor for infant and young child morbidity and mortality. A better understanding of the factors that influence EBF is important in order to promote appropriate infant feeding practices. The return to work due to short maternity leave time may hinder employed mothers from breastfeeding their infants exclusively for the recommended six months duration. Methods A community based comparative cross-sectional study was conducted from January to February 2016 in the Fafan zone, of the Somali Regional State, of Ethiopia. A total of 558 mothers with infants from ages 3-5 months, living in the five districts (Jigjiga city, Kebribeyah town, Aubere town, Bombas town and Babile) were included in the analysis. Logistic regression models were used to examine the effect of maternal employment on EBF practice. Results This study has demonstrated a 24.8 and 82.9% prevalence of EBF practices among employed and unemployed mothers of index infants of 3-5 months respectively in the 24 h preceding the survey. Unemployed mothers were accounted for thusly: [Adjusted OR = 26.5; 95% CI (13.6, 51.6). Other adjustments included monthly income of 500-2000 birr [Adjusted OR = 2.7; 95% CI (1.4, 5.2)]; monthly income of 2001-3500 birr [Adjusted OR = 2.2; 95% CI (1.2, 4.0)]; timely initiation of breastfeeding [Adjusted OR = 2.6; 95% CI (1.4, 4.8)]; maternal education (secondary and higher) [Adjusted OR = 3.8; 95% CI (1.5, 9.5)]; having an index infant aged 3 months [Adjusted OR = 2.2; 95% CI (1.2, 4.1)], and having an index infant aged 4 months [Adjusted OR = 2.2; 95% CI (1.2, 3.8)] were found to be significantly associated with exclusive breastfeeding practice. Conclusion Exclusive breastfeeding practices were very low among mothers employed in governmental and non-governmental organizations in the study area. Therefore, maternal employment may be hindering Exclusive breastfeeding practices. Thus, establishing breastfeeding-friendly working environment; and Information, Education and Communication programs should be provided, particularly for working mothers to promote exclusive breastfeeding practices.